Comparative Study of Nacl-Tolerance Mechanisms in Acidophilic Iron-Oxidizing Bacteria and Archaea - Levican-Jaque, G; Rivera-Araya, J (Trans Tech Publications Ltd, 2017)
Chloride leaching is considered a promising alternative method to recover copper from chalcopyrite and other primary copper sulfides, because it favors the leaching kinetics and avoids passivation of minerals. Nevertheless, chloride ions are highly toxic for iron-oxidizing microorganisms that participate in the bioleaching process. A comparative genomic analysis was carried out based on the complete genomes of bacteria belonging to Nitrospirae, Firmicutes, Actinobacteria and Proteobacteria phyla, and of archaea belonging to Euryarchaeota and Crenarchaeota was carried out to identify molecular determinants involved in chloride tolerance of acidophilic iron-oxidizing microorganisms. The results obtained showed that representative Nitrospirae and Firmicutes harbor genes for the biosynthesis and uptake of compatible solutes such as ectoine, trehalose and potassium, which have been shown to have a role in salt tolerance. Microorganisms belonging to other phyla harbor genes for potassium transporters, but no genes for compatible solutes were detected. In agreement with the bioinformatic results, minimum inhibitory concentration (MIC) determinations and growth kinetics experiments showed that Leptospirillum ferriphilum (Nitrospirae) was more tolerant to NaCl than Acidithiobacillus ferrooxidans (Proteobacteria). Furthermore, it was observed that the addition of 0.5 mM ectoine to the L. ferriphilum culture stimulated growth in the presence of 100 mM NaCl. On the contrary, ectoine had no effect on the growth of At. ferrooxidans. These results suggest that ectoine and likely trehalose could play a key role in chloride tolerance in L. ferriphilum. conferring adaptative advantages compared to A. ferrooxidans and possibly other iron-oxidizing microorganisms. © 2017 Trans Tech Publications, Switzerland.